Dampak anggaran pendidikan terhadap perekonomian Indonesia: Analisis input-output - Sintiana Wijayanti; Ariella Kristiahadi; Belinda Fiona Anggereni; Ritma Ritma; Sotya Fevriera (Nur Science Institute, 2026)
This research analyzes the impact of the 2025 education budget on Indonesian economic activity using Input-Output (IO) analysis. This research utilized data from the Indonesia IO Table for 2020 on 17 products, on the population aged 15 years and over who worked in the past week by main job field, and on the GDP deflator. This research finds that the relationship between the Education Service and other sectors is weak. It makes a significant difference in the magnitude of the Education Service’s impact compared to other sectors. Outside the Education Service, the two sectors that are always among the top four in terms of impact on output, gross value added, labor income, and labor absorption are the Manufacturing Industry and the Trade and Vehicle Repair. This research finds that sectors experiencing a small change in the absolute value of output may experience a big percentage change in output. The relatively low impact of the education budget on other sectors confirms that it will have a significant effect on the economy over the long term.